Photovoltaic system design procedures, tools and applications - Deambi, Suneel (CRC Press, Taylor & Francis Group, 2016)
The book encompasses civil, mechanical, electrical, geotechnical, and power systems engineering and is useful to industry professionals involved in solar power plant design.